2016
DOI: 10.1088/0957-0233/27/11/115012
|View full text |Cite
|
Sign up to set email alerts
|

A metrological approach to improve accuracy and reliability of ammonia measurements in ambient air

Abstract: 21Keywords 22 ammonia in ambient air, traceability, reference gas standards, optical transfer standard, validation and testing 23 infrastructure 24 Abstract 25The environmental impacts of ammonia (NH 3 ) in ambient air have become more evident in the recent decades, 26 leading to intensifying research in this field. A number of novel analytical techniques and monitoring 27 instruments have been developed, and the quality and availability of reference gas mixtures used for the 28 calibration of measuring instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 34 publications
(48 reference statements)
2
25
0
Order By: Relevance
“…This has been evidenced by Yokohata et al (1985) for CCl 4 and CH 3 CCl 3 in very dry mixtures (i.e. likely less than 750 nmol mol −1 of water vapour), who also experimentally showed that adding water vapour to the cylinder annulled this adsorption, water vapour being an excellent competitor for adsorption sites on a metal surface (Vaittinen et al, 2013;Pogàny et al, 2016).…”
Section: Cryo-fillingmentioning
confidence: 84%
“…This has been evidenced by Yokohata et al (1985) for CCl 4 and CH 3 CCl 3 in very dry mixtures (i.e. likely less than 750 nmol mol −1 of water vapour), who also experimentally showed that adding water vapour to the cylinder annulled this adsorption, water vapour being an excellent competitor for adsorption sites on a metal surface (Vaittinen et al, 2013;Pogàny et al, 2016).…”
Section: Cryo-fillingmentioning
confidence: 84%
“…This is much better than the expanded uncertainty of reference gas mixtures, estimated to be on the order of 2 to 4 % for SIO standards (Scripps Institution of Oceanography, e.g. Prinn et al, 2000), 0.3 to 3 % for NIST (National Institute of Standard and Technology, Rhoderick et al, 2015) and 0.6 to < 2 % for NOAA (Hall et al, 2007;Montzka et al, 2015;Lim et al, 2017), as examples. Given this technical state of the art, monitoring networks have developed a so-called "primary calibration scale" system, in which all stations of a specific network are anchored to the same suite of primary reference gas mixtures with a calibration chain as short as possible.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, based on these measurements and using atmospheric transport modelling, emissions can be quantified ("top-down" estimation, e.g. Prinn et al, 2000;Rigby et al, 2010;Brunner et al, 2017). The comparison of top-down reconstructions with bottom-up inventories shows agreement for some gases but also discrepancies that can be considerable for others (Weiss and Prinn, 2011;Lunt et al, 2015;Hu et al, 2016;Simmonds et al, 2016;Sherry et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations